2015
DOI: 10.5588/ijtld.14.0516
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis and excess alcohol use in the United States, 1997–2012

Abstract: SUMMARY BACKGROUND Excess alcohol use among tuberculosis (TB) patients complicates TB control strategies. OBJECTIVES To characterize the role of excess alcohol use in TB control, we describe the epidemiology of excess alcohol use and TB in the United States among those aged ≥15 years. DESIGN Using data reported to the National Tuberculosis Surveillance System, 1997–2012, we examined associations between excess alcohol use and TB treatment outcomes and markers for increased transmission (involvement in a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
4
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 41 publications
3
31
4
1
Order By: Relevance
“…Excessive alcohol intake is also associated with lower rates of negative sputum culture conversion and higher rates of mortality (Volkmann et al 2015). In the present study, the gastrectomy group had a higher prevalence of alcohol consumption than the control group (53.3% vs. 6.7%; P < 0.001).…”
Section: Discussionsupporting
confidence: 40%
“…Excessive alcohol intake is also associated with lower rates of negative sputum culture conversion and higher rates of mortality (Volkmann et al 2015). In the present study, the gastrectomy group had a higher prevalence of alcohol consumption than the control group (53.3% vs. 6.7%; P < 0.001).…”
Section: Discussionsupporting
confidence: 40%
“…Recently, the Nigeria National TB Control Programme and its donor partners have commenced the scale-up of availability and accessibility to improved methods for TB diagnosis and effective treatment regimen [5, 6]. While those efforts are needed and well deserved in Nigeria, there are limited pragmatic policy actions to tackle emerging risk factors for TB at the population level, including diabetes [7, 8], alcohol intake [811] and tobacco smoking [8, 12]. Country-specific epidemiologic studies which investigate trends in TB disease burden and the attributable risk factors for TB would be useful for public health experts and policy-makers to strengthen TB control and preventive efforts.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] The present study has observed a prevalence of alcohol use among TB patients to be 20.5% (95% CI=13.18% to 27.82%) and all of them were males. However, no significant associated was noted between alcohol use and the type of TB.…”
Section: Resultsmentioning
confidence: 94%